Edukasi Upaya Pencegahan Prilaku Bullying pada Siswa di Sekolah Dasar Negeri 1 Pelambua - Irawan, Rifal; Julfikar; Asrul; Oktoria, Pegi; Nugroho, Dwi Kristiana; Masni; Mutmainah; Hikma Jaya, Andi; Nurfadillah; Asani, Nur Lina Putri; Rusni; Kamur, Sudarwin; Awal, Samsi; Iskandar, Ahmad; Chairuddin; Ernawati; Permana , Dian (Wahana Dedikasi: Jurnal PkM Ilmu Kependidikan, 2024)
Bullying is the act of using power to harm a person or group of people both verbally and psychologically, so that the victim feels depressed, traumatized and helpless. There are several impacts of bullying that need to be aware of because they can affect the mental health of both victims and perpetrators, such as triggering emotional disorders, mental problems, sleep disorders, decreased achievement, and so on. The purpose of this study is to increase students' awareness and understanding of the importance of respecting each other and the negative impact of bullying behavior. In this research, the methods used are literature studies and case studies. The results obtained were an increase in students' understanding of the definition and forms of bullying, including physical, verbal, and social bullying. Before the socialization, most students thought that bullying was only limited to physical violence, but after the socialization, they began to realize that actions such as mocking, excluding, and spreading rumors were also included in bullying behavior. Based on the results of the above research, it can be concluded that education on bullying prevention has not only succeeded in increasing student awareness, but also encouraging active participation from all elements of the school in creating a safer and more positive environment.